Hopes and Fears of First-Year Freshman College Students during the COVID-19 Pandemic - Cláudia Andrade; Joana L. Fernandes (MDPI AG, 2022)
The COVID-19 pandemic made the experience of being a first-year freshman college student unique. This study aims to analyze the hopes and fears of these students concerning their current life and future goals. Participating students completed the Hopes & Fears questionnaire. Results showed that students' hopes and fears were mainly connected with domains of education and the global/collective dimension, followed by personal and family members' health. Two new categories emerged, self-fulfillment and solidarity, reflecting the importance of the contextual dimension that these students were navigating. The findings of the current study contribute to the research of college students' hopes and fears towards their future and accounts for the analyses of this topic as we progress to a post-pandemic phase.